Leveraging COBIT 2019 Framework to Implement IT Governance in Business Process Outsourcing Company - Melissa Indah Fianty; Maximillian Brian (Universitas Bina Darma, 2023)
The company specializes in delivering information and technology services to businesses operating in the same industry. Recognizing the pivotal role of information technology in achieving its vision, mission, and goals, the company emphasizes the proper implementation of IT governance to drive overall company success. To evaluate the management of IT resources, the study employs the COBIT-2019 framework for measurement. The data collection approach encompasses interviews, questionnaires, observation, and document analysis. The findings indicate that most IT governance processes currently operate at level 2 capability. However, the company aspires to reach level 3 for these processes. Consequently, recommendations are proposed to enhance these processes based on the best practices outlined in COBIT-2019. Key suggestions include implementing performance measurements and facilitating access to knowledge repositories to foster skill and competency development.